BER and PAPR Reduction in OFDM System By Using Companding Technique (International Journal of Engineering and Computer Science, 2015)
One of the challenging issues for OFDM is its high Peak to Average Power Ratio (PAPR) which limits itsapplications in wireless communication systems using multicarrier modulation technique as OFDM, whichreduces the efficiency of transmit high power amplifier. In this paper, we introduced companding techniquewith different value of µ. Later in this paper, simulation results show the PAPR and BER performance andthen comparison by changing modulation scheme without any technique and with companding technique areevaluated.